Odpowiedź :
Odpowiedź:
(2
6
1
−1
3
1
)×2
5
2
=(
6
13
−
3
4
)×
5
12
=(
6
13
−
6
8
)×
5
12
=
6
5
×
5
12
=
6
12
=2
2 \frac{2}{7} \times 7 - {(3 \frac{1}{2}) }^{2} = \frac{16}{7} \times 7 - \frac{49}{4} = 16 - 12 \frac{1}{4} = 3 \frac{3}{4}2
7
2
×7−(3
2
1
)
2
=
7
16
×7−
4
49
=16−12
4
1
=3
4
3
( {2 \frac{1}{2} - 1 \frac{1}{3} ) }^{2} - ( { \frac{5}{6} )}^{2} = ( { \frac{5}{2} - \frac{4}{3}) }^{2} - \frac{25}{36} = ( { \frac{15}{6} - \frac{8}{6} ) }^{2} - \frac{25}{36} = {( \frac{7}{6}) }^{2} - \frac{25}{36} = \frac{49}{36} - \frac{25}{36} = \frac{24}{36} = \frac{2}{3}(2
2
1
−1
3
1
)
2
−(
6
5
)
2
=(
2
5
−
3
4
)
2
−
36
25
=(
6
15
−
6
8
)
2
−
36
25
=(
6
7
)
2
−
36
25
=
36
49
−
36
25
=
36
24
=
3
2
{(1 \frac{1}{2} )}^{3} - {( \frac{2}{3}) }^{3} - \frac{1}{5} \times 2 \frac{1}{6} = ( { \frac{3}{2}) }^{3} - \frac{8}{27} - \frac{1}{5} \times \frac{13}{6} = \frac{27}{8} - \frac{8}{27} - \frac{13}{30} = \frac{729}{216} - \frac{64}{216} - \frac{13}{30} = \frac{665}{216} - \frac{13}{30} = \frac{19950}{6480} - \frac{2808}{6480} = \frac{17142}{6480} = 2 \frac{4182}{6480} = 2 \frac{2091}{3240} = 2 \frac{697}{1080}(1
2
1
)
3
−(
3
2
)
3
−
5
1
×2
6
1
=(
2
3
)
3
−
27
8
−
5
1
×
6
13
=
8
27
−
27
8
−
30
13
=
216
729
−
216
64
−
30
13
=
216
665
−
30
13
=
6480
19950
−
6480
2808
=
6480
17142
=2
6480
4182
=2
3240
2091
=2
1080
697